Comportamento no solo dos herbicidas diuron, hexazinone e sulfometuron- methyl aplicados isoladamente e em mistura - Medeiros , Rita de Cassia Araújo de (Universidade Federal Rural do Semi-Árido, 2020)
The current agricultural management system has increased the use of herbicide and pesticide combinations, as this increases efficiency and broadens the spectrum of weed control, with formulated mixtures frequently used in sugarcane fields. The frequent, and often incorrect, use of these products can pose a threat of contamination of surface and groundwater. This research studied the influence of the commercial application of the herbicides diuron, hexazinone and sulfometuron-methyl, in the retention, persistence and leaching processes, in the soils of the sugarcane regions of Brazil. The sorption and desorption study was carried out using the “Batch Equilibrium” method. Herbicide degradation was evaluated for 180 days to determine the half-life (t1/2). The leaching tests were conducted in columns. The selected herbicides and mixtures were quantified by Ultra High Performance Liquid Chromatography coupled to the Mass Spectrometer (LC-MS / MS). The additives present in commercial formulations favor leaching of herbicides diuron, hexazinone and sulfometuron-methyl, and mix in studied soils, with standard variations, showing the importance of carrying out tests that predict or use the herbicides used in the field. Thus, it is possible to determine with greater precision or effect the commercial application on the destination of the active substance in the soil, minimizing the risks of groundwater contamination. Sulfometuron-methyl in the mixture shows greater leaching compared to the isolated application in LV, CX and RQ, with greater evidence for mixtures that use hexazinone in commercial application. The commercial herbicides used in agricultural fields have greater mobility in soils, on the other hand, due to greater persistence in the soil, which can harm subsequent crops and affected by the greater potential for leaching, causing an increase in the risks of surface water contamination and external
Keywords: Processos de retenção; Cana-de-açúcar; Controle químico; Contaminação ambiental; Retention processes; Sugarcane; Chemical control; Environmental contamination; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO